ANALISIS DAMPAK PANDEMI COVID 19 BAGI RASIO LIKUIDITAS BANK BUKOPIN SYARIAH - Itsnaini Chusnul Khotimah (Program Studi Perbankan Syariah, 2021)
This study aims to describe the results of the comparison of liquidity ratios at Bank Bukopin Syariah from 2018, 2019 and 2020. Where in 2018 and 2019, the Covid 19 pandemic has not occurred and in 2020 the Covid 19 pandemic has occurred. The author wants to know whether a pandemic has occurred. Covid 19 has a significant impact on the liquidity ratio of Bank Bukopin Syariah. The author uses descriptive qualitative research methods based on the theory obtained through literature study. The results of this study indicate that there has been a decrease in the three liquidity ratios from 2018 to 2019 and 2019 to 2020. Even though the decline that occurred was not too significant and made Bank Bukopin Syariah declared in poor condition in 2020 because of the three ratios are below average standard. So the Covid 19 pandemic that occurred in 2020 had an influence on the liquidity ratio factor of Bank Bukopin Syariah even though Bank Bukopin Syariah was still able to carry out its obligations to pay current debts and the Covid 19 pandemic did not affect the performance and ability of Bank Bukopin Syariah.